Policy-Makers Responses to Food Price Crises: Results from a 14-Country Political Economy Study - Pinstrup-Andersen, Per (2013)
Policy Seminar presentation by Per Pinstrup-Andersen, Cornell University at IFPRI Policy Seminar on "Policymakers’ Responses to Food Price Crises" May 3, 2013